Brazil-Portugal Comparison: Education, Health and Social Development in light of the Sustainable Development Goals - Felipa Rafaela Amadigi; Monica Motta Lino; Rosani Ramos Machado; Ianka Cristina Celuppi; Carla Sílvia Fernandes; Maria Manuela Martins; Denise Elvira Pires de Pires (Revista Brasileira de Enfermagem)
ABSTRACT Objective: to comparatively analyze the health, education and social development systems of Brazil and Portugal, their relationship with the Sustainable Development Goals and the Organization for Economic Cooperation and Development averages. Method: exploratory and descriptive qualitative research, through documentary analysis. The indicators address health, education and social development, considering life expectancy, mortality, prevalence of chronic diseases, literacy, educational performance and poverty rates. Results: indicate significant differences between countries. Portugal presents better indicators in life expectancy, educational quality and poverty rates, whereas Brazil faces greater challenges in chronic diseases and equity in access to healthcare services. Final considerations: the importance of public policies adapted to local realities and the need for a strategic vision for healthcare systems aligned with the Sustainable Development Goals, in addition to the need for continuous investments and integration of digital health for efficient and equitable systems, stand out.